2014
DOI: 10.1097/pap.0000000000000032
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Transplantation

Abstract: Hematopoietic stem cell transplantation (HCT), formerly known as bone marrow transplantation, is an integral part of treatment for many hematological malignancies. HCT is associated with several complications and comorbidities with differential effects on a wide spectrum of organs and tissues. We present an update on HCT-associated complications such as graft versus host disease (GVHD) and infection, with focus on the surgical pathology of the gastrointestinal (GI) tract, liver, and lung. Although the grading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 134 publications
1
11
0
Order By: Relevance
“…Interstitial and alveolar pneumonitis, perivascular lymphocytic inflammation, and lymphocytic bronchiolitis were observed in the “TBI/BMT” group ( Fig 3A ). These findings were compatible with the clinically defined “idiopathic pneumonia syndrome (IPS)”, encompassing widespread alveolar injury in the absence of infection, cardiac dysfunction, renal failure, and iatrogenic fluid overload, and affecting 5% to 25% of allo-HSCT recipients [ 29 31 ]. By the semi-quantitative scoring system of IPS [ 26 ], it was clearly demonstrated that NB-UVB irradiation ameliorated IPS with statistical significance (p = 0.0019), as shown in Fig 3B .…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Interstitial and alveolar pneumonitis, perivascular lymphocytic inflammation, and lymphocytic bronchiolitis were observed in the “TBI/BMT” group ( Fig 3A ). These findings were compatible with the clinically defined “idiopathic pneumonia syndrome (IPS)”, encompassing widespread alveolar injury in the absence of infection, cardiac dysfunction, renal failure, and iatrogenic fluid overload, and affecting 5% to 25% of allo-HSCT recipients [ 29 31 ]. By the semi-quantitative scoring system of IPS [ 26 ], it was clearly demonstrated that NB-UVB irradiation ameliorated IPS with statistical significance (p = 0.0019), as shown in Fig 3B .…”
Section: Resultssupporting
confidence: 60%
“…IPS is widespread alveolar injury in the absence of infection, cardiac dysfunction, renal failure, and iatrogenic fluid overload, and affects 5% to 25% of allo-HSCT recipients [ 29 31 ]. The mortality rate of IPS in allo-HSCT recipients ranges from 60 to 80% overall, and is greater than 95% among patients requiring mechanical ventilation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because leukotrienes may cause significant lung dysfunction ( Cingi et al, 2015 ; Qian et al, 2015 ; Sekioka et al, 2015 ; Ee et al, 2016 ; Shigematsu et al, 2016 ) and the lung is a target organ of GVHD (Ferrara, 2009; Haddad, 2013 ; Xu et al, 2013 ; Kambham et al, 2014 ), we evaluated the effect of treatment with zileuton, CP-105,696, and montelukast in the pulmonary injury that follows GVHD. We observed that there was significant pulmonary injury at the onset of mortality caused by the induction of GVHD (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary complications are responsible for ∼70% of morbidity and 30% of mortality after GVHD ( Yousef et al, 2013 ). In humans, the disease tends to be more often chronic and characterized primarily by an obliterating bronchiolitis ( Haddad, 2013 ; Xu et al, 2013 ; Yousef et al, 2013 ; Kambham et al, 2014 ). Regardless, we observed that pulmonary injury in our system was acute at onset and occurred at significant levels during the onset of lethality.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of GI aGVHD is traditionally based on clinical manifestations and endoscopic biopsy [ 3 ]. Manifestations of GI aGVHD is characterized by watery diarrhea, nausea, anorexia and abdominal cramps, but these non-specific symptoms may mimic infection [ 3 , 4 ]. Digestive endoscopy is often restrained by poor general patient health after HSCT, and crypt apoptosis in a mucosal biopsy is not specific for GI aGVHD.…”
Section: Introductionmentioning
confidence: 99%